The Phenomenon of Fear of Missing Out (FOMO) in Hangout Activities at Pasaraya Blok M - Nabilla Diandra Prakasa; Adella Dwi Anjani; Zahrina Izzati; Fadillah Dini Rasasti; Maydina Amanatul Latifah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Fear of Missing Out (FOMO) is the fear of feeling